Implementation of Social Emotional Learning to Manage Academic Stress and Its Impact on Senior High School Students' Well-Being in Coordination System Topic - Qisthi, Naufalia; Rahmat, Adi; Kusnadi, Kusnadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effectiveness of Social Emotional Learning (SEL) in managing academic stress and its influence on well-being and conceptual understanding of the coordination system material. This study employs a mixed-methods embedded approach, involving pretests, posttests, and qualitative interviews. The population of this research is senior high school students in one public school in Ciamis Regency. The sample was selected using purposive sampling, in which two classes of grade XI students were chosen based on the consideration that their Biology lesson schedules were relatively similar and their average academic stress scores were nearly equal. These classes were then assigned as the experimental group and the control group. The experimental group underwent SEL intervention, while the control group followed the conventional learning process. Data collection techniques included academic stress questionnaires, conceptual understanding tests, and well-being interviews. The quantitative data were analyzed using paired t-tests and independent t-tests, while qualitative data were analyzed through thematic coding. The results revealed a significant decrease in academic stress (p < 0.05) and improvement in conceptual understanding in the experimental group. The qualitative findings highlighted enhanced well-being in terms of emotional regulation, self-awareness, and interpersonal skills. This study concludes that SEL can be an effective approach to reducing academic stress and fostering holistic development in high school students, and it is recommended for broader implementation in educational practices.